Clinical effects of the use of a bipolar vessel sealing device for soft palate resection and tonsillectomy in dogs, with histological assessment of resected tonsillar tissue - Cook, DA; Moses, PA; Mackie, JT (Australian veterinary journal, 2015)
OBJECTIVE: To investigate whether soft palate resection and tonsillectomy with a bipolar vessel sealing device (BVSD) improves clinical respiratory score. To document histopathological changes to tonsillar tissue following removal with a BVSD. METHODS & RESULTS: Case series of 22 dogs with clinical signs of upper respiratory obstruction related to brachycephalic airway syndrome. Soft palate and tonsils were removed using a BVSD. Alarplasty and saccullectomy were also performed if indicated. A clinical respiratory score was assigned preoperatively, 24‐h postoperatively and 5 weeks postoperatively. Excised tonsillar samples were measured and then assessed histologically for depth of tissue damage deemed to be caused by the device. Depth of tissue damage was compared between two power settings of the device. Soft palate resection and tonsillectomy with a BVSD lead to a significant improvement in respiratory scores following surgery. Depth of tissue damage was significantly less for power setting 1 compared with power setting 2. Using power setting 1, median calculated depth of tonsillar tissue damage was 3.4 mm (range 1.2–8.0). One dog experienced major complications. CONCLUSION: Soft palate resection and tonsillectomy with a BVSD led to significant improvement in clinical respiratory score.